Facile Enzymatic Synthesis of Phosphatidylthreonine Using an Engineered Phospholipase D. Issue 6 (24th April 2018) - Damnjanović, Jasmina; Matsunaga, Nozomi; Adachi, Masaatsu; Nakano, Hideo; Iwasaki, Yugo
Abstract : Here is described the newly established method for direct enzymatic synthesis of phosphatidylthreonine (PtdThr). It is the first report on enzymatic synthesis of this rare phospholipid. It utilizes phospholipase D (PLD)‐catalyzed transphosphatidylation, in which the head group of phosphatidylcholine (PtdCho) is exchanged to L‐Threonine (L‐Thr). An attempt to catalyze the reaction between PtdCho and L‐Thr using wild‐type PLD is not successful, possibly because the secondary hydroxyl group of L‐Thr is not accessible to the enzyme. To synthesize Ptd‐L‐Thr, the natural PtdThr isomer, engineered PLD variants active toward secondary hydroxyls of inositol are screened for their ability to accept L‐Thr. Six variants are identified as positive, among which 187F/191Y/385L (FYL) shows highest activity. After optimizing the reaction parameters, Ptd‐L‐Thr content reaches approximately 30 mol%. The product is isolated by column chromatography with the overall yield of 5.2%, and its structure is confirmed by NMR. In addition, the FYL variant can also react on some stereoisomers of threonine, L‐ allo ‐Thr, and D‐ allo ‐Thr as well as L‐Thr, but not D‐Thr. Ligand docking simulation explains the enzyme's preference toward these stereoisomers; L‐, L‐ allo ‐, and D‐ allo ‐Thr can bind to the enzyme's active site in a productive orientation, whereas D‐Thr binds in a position which makes the reaction impossible to proceed. Practical Applications : The enzymatic method enables one‐step synthesis of PtdThr from PtdCho and L‐Threonine without any protection/deprotection steps, thereby being much more simple and less hazardous than the currently used chemical methods. The synthesized PtdThr can be isolated in pure form and used as a reagent for elucidation of its biological functions. A method for one‐step enzymatic synthesis of phosphatidylthreonine (PtdThr) is described. It uses the head group exchange of phosphatidylcholine (PtdCho) with Threonine(Thr) catalyzed by an engineered phospholipase D (PLD). The enzyme can accept some stereoisomers of Thr, that is, L‐Thr, L‐allo‐Thr, and D‐allo‐Thras the substrates to give the corresponding PtdThr, but notD‐Thr. Docking simulation explainsthe enzyme's preference toward thesestereoisomers; L‐, L‐allo‐, and D‐allo‐Thr can bind to the enzyme's active site in a productive orientation, whereas D‐Thrbinds in a non‐productive orientation which makes the reaction impossible to proceed. Abstract : A method for one‐step enzymatic synthesis of phosphatidylthreonine (PtdThr) is described. It uses the head group exchange of phosphatidylcholine (PtdCho) with Threonine(Thr) catalyzed by an engineered phospholipase D (PLD). The enzyme can accept some stereoisomers of Thr, that is, L‐Thr, L‐allo‐Thr, and D‐allo‐Thras the substrates to give the corresponding PtdThr, but notD‐Thr. Docking simulation explainsthe enzyme's preference toward thesestereoisomers; L‐, L‐allo‐, and D‐allo‐Thr can bind to the enzyme's active site in a productive orientation, whereas D‐Thrbinds in a non‐productive orientation which makes the reaction impossible to proceed.